African Management Model Research - Testing Import - (:unkn) unknown (My University, 2007)
Since the late 1980s, some researchers have attempted to develop a specific model of management in Africa: African management. This model starts from the premise that the implementation of Western management methods in Africa has failed to improve the performance of African enterprises.
Keywords: African Research; Management africain; Afrique